The Effect of Loose Parts Media on Early Childhood Naturalist Intelligence - Priyanti, Nita; Jhoni Warmansyah (Jurnal Pendidikan Usia Dini, 2021)
Naturalist intelligence of early childhood has a very big role in today's modern age as the basis for children to have environmental-loving behaviour. The purpose of this study was to determine the effect of Loose Parts learning media on the naturalist intelligence. This study uses a quasi-experimental method with data collection techniques through multiple intelligence tests of children's intelligence instruments. The subjects of this study were 17 children aged 5-6 years. The results showed that there was a significant effect of giving Loose Parts media to the naturalist intelligence of early childhood after seeing a difference between pre-test and post-test. The use of natural-based Loose Parts media can be a means for teachers to increase children's naturalist intelligence in kindergarten and be a development of conventional media made from manufacturers in the learning cycle so far. For further research, it is recommended to look at the influence of other factors on naturalist intelligence in early childhood. Keywords: Early Childhood, Loose Parts, Naturalist Intelligence References: Aljabreen, H. (2020). Montessori, Waldorf, and Reggio Emilia: A Comparative Analysis of Alternative Models of Early Childhood Education. International Journal of Early Childhood, 52(3), 337–353. https://doi.org/10.1007/s13158-020-00277-1 Anjari, T. Y., & Purwanta, E. (2019). Effectiveness of the Application of Discovery Learning to the Naturalist Intelligence of Children About the Natural Environment in Children Aged 5-6 Years. International Conference on Special and Inclusive Education (ICSIE 2018), 296, 356–359. https://doi.org/10.2991/icsie-18.2019.65 Armstrong, T. (2002). You’re Smarter Than You Think: A Kid’s Guide to Multiple Intelligences. Free Spirit Publishing Inc., 217 Fifth Ave., North, Suite 200, Minneapolis, MN 55401-1299. Asih, S., & Susanto, A. (2017). Peningkatan Kecerdasan Naturalis Pada Anak Usia 5-6 Tahun Melalui Model Pembelajaran Di Sentra Bahan Alam. Yaa Bunayya: Jurnal Pendidikan Anak Usia Dini, 1(1). https://doi.org/10.24853/yby.1.1.33-38 Ata-Akturk, A., & Sevimli-Celik, S. (2020). Creativity in early childhood teacher education: Beliefs and practices. International Journal of Early Years Education, 1–20. https://doi.org/10.1080/09669760.2020.1754174 Azizah, E. N. (2021). Peningkatan Kecerdasan Naturalis Melalui Kolase Bahan Alam Pada Anak Kelompok A TK Kemala Bhayangkari 54 Ngawi. Journal of Childhood Education, 5(1). https://doi.org/10.30736/jce.v5i1.491 Damayanti, A., Akbar, M., & Yufiarti, Y. (2019). The Interaction Effect of Learning Methods and Naturalist Intelligence Toward Children’s Art Creativity. Proceedings of the First International Conference on Technology and Educational Science. https://doi.org/10.4108/eai.21-11-2018.2282278 Diana, H., Diana, S., & Wulan, A. R. (2019). Hubungan antara kecerdasan naturalis dengan sikap lingkungan. Konferensi Internasional Tentang Biologi Dan Sains Terapan (ICOBAS). Ebrahimi, T. (2017). Effect of Technology on Education in Middle East: Traditional Education Versus Digital Education. In Digital Transformation in Journalism and News Media (pp. 519–531). Springer International Publishing. https://doi.org/10.1007/978-3-319-27786-8_38 Faridy, F., & Rohendi, A. (2021). The Role of Parents in Engaging Early Childhood to Implement 3R (Reduce, Reuse, Recycle). Proceedings of the International Conference on Engineering, Technology and Social Science (ICONETOS 2020), 529(Iconetos 2020), 483–486. https://doi.org/10.2991/assehr.k.210421.070 Fatonah, S., & Prasetyo, Z. K. (2018). Science Learning Model To Improve Naturalist Intelligence For Early Childhood. Sunan Kalijaga International Journal on Islamic Educational Research, 1(1), 34–50. https://doi.org/10.14421/skijier.2017.2017.11-03 Flannigan, C., & Dietze, B. (2018). Children, Outdoor Play, and Loose Parts. Journal of Childhood Studies, 53–60. https://doi.org/10.18357/jcs.v42i4.18103 Furi, A. Z., Harmawati, Denok, M., & B.A. (2019). Meningkatkan Kemampuan Kognitif melalui Penerapan Metode Eksperimen Menggunakan Media Loose Parts pada Anak Kelompok B. Emphaty Cons: Journal of Guidance and Counseling, 1(2), 7–19. Gardner, H. (1994). Frames Of Mind. New York, NY, Basic Books. Gibson, J. L., Cornell, M., & Gill, T. (2017). A Systematic Review of Research into the Impact of Loose Parts Play on Children’s Cognitive, Social and Emotional Development. School Mental Health, 9(4), 295–309. https://doi.org/10.1007/s12310-017-9220-9 Gold, Z. S., & Elicker, J. (2020). Engineering Peer Play: A New Perspective on Science, Technology, Engineering, and Mathematics (STEM) Early Childhood Education (pp. 61–75). https://doi.org/10.1007/978-3-030-42331-5_5 Gull, C., Bogunovich, J., Goldstein, S. L., & Rosengarten, T. (2019). Definitions of Loose Parts in Early Childhood Outdoor Classrooms: A Scoping Review Carla Gull Jessica Bogunovich Suzanne Levenson Goldstein Tricia Rosengarten. International Journal of Early Childhood Environmental Education Copyright, 6(3), 37–52. Hafizotun, L. (2017). Pemberdayaan Sentra Bahan Alam Untuk Mengembangkan Kecerdasan Naturalis Anak Usia Dini Di Taman Kanak-Kanak Islam Terpadu Nurul Ilmi Kota Jambi. Jurnal Al-Ashlah, 1(Vol 1, No 2 (2017)). Hapidin, Gunarti, W., Pujianti, Y., & Siti Syarah, E. (2020). STEAM to R-SLAMET Modification: An Integrative Thematic Play Based Learning with R-SLAMETS Content in Early Child-hood Education. JPUD - Jurnal Pendidikan Usia Dini, 14(2), 262–274. https://doi.org/10.21009/JPUD.142.05 Hartika, D., Diana, S., & Wulan, A. R. (2019). Relationship between naturalist intelligence with environmental attitude. 060017. https://doi.org/10.1063/1.5115717 Herwati, Y. (2019). Pengaruh Permainan Ludo Bergambar Terhadap Kecerdasan Naturalis Anak di Taman Kanak-kanak Tunas Bangsa Bukittinggi. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 4(1), 428. https://doi.org/10.31004/obsesi.v4i1.358 Houser, N. E., Cawley, J., Kolen, A., Rainham, D., Rehman, L., Turner, J., Kirk, S., & Stone, M. (2019). A Loose Parts Randomized Controlled Trial to Promote Active Outdoor Play in Preschool-aged Children: Physical Literacy in the Early Years (PLEY) Project. Methods and Protocols, 2(2), 27. https://doi.org/10.3390/mps2020027 Houser, N. E., Roach, L., Stone, M. R., Turner, J., & Kirk, S. F. L. (2016). Let the Children Play: Scoping Review on the Implementation and Use of Loose Parts for Promoting Physical Activity Participation. AIMS Public Health, 3(4), 781–799. https://doi.org/10.3934/publichealth.2016.4.781 Imamah, Z., & Muqowim, M. (2020). Pengembangan kreativitas dan berpikir kritis pada anak usia dini melalui motode pembelajaran berbasis STEAM and loose part. Yinyang: Jurnal Studi Islam Gender Dan Anak, 263–278. https://doi.org/10.24090/yinyang.v15i2.3917 Jamaris, M. (2018). Pengembangan Instrumen Baku Kecerdasan Jamak Anak Usia Dini. PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 25(2), 123–137. https://doi.org/10.21009/parameter.252.08 Juniarti, Y. (2015). Peningkatan Kecerdasan Naturalis Melalui Metode Kunjungan Lapangan (Field Trip). JPUD - Jurnal Pendidikan Usia Dini, 9(2). https://doi.org/10.21009/JPUD.092.05 Karwowski, M., Kaufman, J. C., Lebuda, I., Szumski, G., & Firkowska-Mankiewicz, A. (2017). Intelligence in childhood and creative achievements in middle-age: The necessary condition approach. Intelligence, 64, 36–44. https://doi.org/10.1016/j.intell.2017.07.001 Keniger, L., Gaston, K., Irvine, K., & Fuller, R. (2013). What are the Benefits of Interacting with Nature? International Journal of Environmental Research and Public Health, 10(3), 913–935. https://doi.org/10.3390/ijerph10030913 Kirkham, J. A., & Kidd, E. (2017). The Effect of Steiner, Montessori, and National Curriculum Education Upon Children’s Pretence and Creativity. The Journal of Creative Behavior, 51(1), 20–34. https://doi.org/10.1002/jocb.83 Kristiawan, M. (2016). Telaah Revolusi Mental Dan Pendidikan Karakter Dalam Pembentukkan Sumber Daya Manusia Indonesia Yang Pandai Dan Berakhlak Mulia. Ta’dib, 18(1), 13. https://doi.org/10.31958/jt.v18i1.274 Latifah, C. N., & Prasetyo, I. (2019). Effectiveness of Educational Game for the Intelligence of Early Childhood Naturalist. Advances in Social Science, Education and Humanities Research, 296(Icsie 2018), 310–314. https://doi.org/10.2991/icsie-18.2019.56 Liani, S., & Barsihanor. (2020). Strategies for Developing Naturalist Intelligence at Nature Schools. Journal of K6 Education and Management, 3(3), 401–410. https://doi.org/10.11594/jk6em.03.03.12 Marsden, E., & Torgerson, C. J. (2012). Article in Oxford Review of Education ·. May 2016. https://doi.org/10.2307/41702779 Maulisa, R., Israwati, & Amri, A. (2016). Meningkatkan Kecerdasan Naturalis Anak Melalui Media Bahan Alam Di Paud It Aneuk Shaleh Ceria Desa Neuheun Kebupaten Aceh Besar. Jurnal Ilmiah Mahasiswa Pendidikan Anak Usia Dini, 1(1), 99–107. Ningrum, Z. B., Soesilo, T. E. B., & Herdiansyah, H. (2018). Naturalistic Intelligence and Environmental Awareness among Graduate Students. E3S Web of Conferences, 68, 02004. https://doi.org/10.1051/e3sconf/20186802004 Nipriansyah, N., Rambat Nur Sasongko, Muhammad Kristiawan, E. S., & Hasanah, P. F. A. (2021). Increase Creativity And Imagination Children Through Learning Science, Technologic, Engineering, Art And Mathematic With Loose Parts Media. Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 4(1). https://doi.org/10.24042/ajipaud.v4i1.8598 Nurfadilah. (2020). Kemampuan Motorik Halus Melalui Kegiatan Kolase Dengan Bahan Loose Part Pada Anak Usia 4-6 Tahun di Bangkinang Kota. Journal on Teacher Education, 2(1). https://doi.org/10.31004/jote.v2i1.1193 Nurhafizah, N. (2018). Development of Naturalist Intelligence of Children in Kindergarten. International Conference of Early Childhood Education (ICECE 2017), 169, 17–20. https://doi.org/10.2991/icece-17.2018.5 Nurjanah, N. E. (2020). Pembelajaran STEM Berbasis Loose Parts Untuk Meningkatkan Kreativitas Anak Usia Dini. Jurnal Ilmiah Kajian Ilmu Anak Dan Media Informasi PUD, 1(1), 19–31. Olsen, H., & Smith, B. (2017). Sandboxes, loose parts, and playground equipment: A descriptive exploration of outdoor play environments. Early Child Development and Care, 187(5–6), 1055–1068. https://doi.org/10.1080/03004430.2017.1282928 Prameswari, T., & Anik Lestariningrum. (2020). Strategi Pembelajaran Berbasis STEAM Dengan Bermain Loose Parts Untuk Pencapaian Keterampilan 4c Pada Anak Usia 4-5 Tahun. Efektor, 7(1), 24–34. https://doi.org/10.29407/e.v7i2.14387 Rahmatunnisa, S., & Halimah, S. (2018). Upaya Meningkatkan Kecerdasan Naturalis Anak Usia 4 – 5 Tahun Melalui Bermain Pasir. Jurnal Pendidikan Anak Usia Dini, 2(1), 67–82. Ramdani, Z. (2017). Increased naturalist intelligence through the use of realia media. Jurnal Golden Age Hamzanwadi University, 1(1), 16–32. Rizkia, N., Hayati, F., & Amelia, L. (2020). Analisis Penggunaan Media Pasir Kinetik Dalam Menstimulasi Kecerdasan Naturalis Pada Anak Kelompok B1 Tk Pertiwi Lhoknga. Jurnal Ilmiah Mahasiswa Pendidikan, 1(1), 1–12. Rocmah, L. I. (2016). Peningkatan Kecerdasan Naturalis Melalui Bermain Messy Play terhadap Anak Usia 5-6 Tahun. PEDAGOGIA: Jurnal Pendidikan, 5(1), 47. https://doi.org/10.21070/pedagogia.v5i1.88 Rueda, L., Benitez, J., & Braojos, J. (2017). From traditional education technologies to student satisfaction in Management education: A theory of the role of social media applications. Information & Management, 54(8), 1059–1071. https://doi.org/10.1016/j.im.2017.06.002 Sari, N. E., & Suryana, D. (2019). Thematic Pop-Up Book as a Learning Media for Early Childhood Language Development. JPUD - Jurnal Pendidikan Usia Dini, 13(1), 43–57. https://doi.org/10.21009/10.21009/JPUD.131.04 Saripudin, A. (2017). Strategi Pengembangan Kecerdasan Naturalis Pada Anak Usia Dini. AWLADY : Jurnal Pendidikan Anak, 3(1). https://doi.org/10.24235/awlady.v3i1.1394 Siregar, N. M. (2018). Peningkatan Kecerdasan Interpersonal Melalui Aktivitas Fisik Anak Usia 4-5 Tahun. JPUD - Jurnal Pendidikan Usia Dini, 12(2), 291–300. https://doi.org/10.21009/JPUD.122.10 Smith-gilman, S. (2018). The Arts, Loose Parts and Conversations. Journal of the Canadian Association for Curriculum Studies, 16(1), 90–103. Sugiyono. (2017). Metode Penelitian Bisnis: Pendekatan Kuantitatif, Kualitatif, Kombinasi, dan R&D. CV. Alfabeta. Suryani, L., & Seto, S. B. (2020). Penerapan Media Audio Visual untuk Meningkatan Perilaku Cinta Lingkungan pada Golden Age. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1), 900–908. https://doi.org/10.31004/obsesi.v5i1.601 Swadley, G. (2021). Any Which Way. . . Loose Parts Play in the Library. Children and Libraries, 19(1), 21. https://doi.org/10.5860/cal.19.1.21 Tremblay, M. S., Gray, C., Babcock, S., Barnes, J., Bradstreet, C. C., Carr, D., Chabot, G., Choquette, L., Chorney, D., Collyer, C., Herrington, S., Janson, K., Janssen, I., Larouche, R., Pickett, W., Power, M., Sandseter, E. B. H., Simon, B., & Brussoni, M. (2015). Position statement on active outdoor play. International Journal of Environmental Research and Public Health, 12(6), 6475–6505. https://doi.org/10.3390/ijerph120606475 Utami, Rohman, A., & Islamiyah, R. (2020a). Introduction of the Surrounding Environment to Stimulate Naturalist Intelligence of Early Childhood. Journal of Physics: Conference Series, 1511(1). https://doi.org/10.1088/1742-6596/1511/1/012070 Vardin, P. A. (2016). Montessori and Gardner’s theory of multiple intelligences. Montessori Life, 15(1), 40. Wahyuni, S., & Reswita, R. (2020). Pemahaman Guru mengenai Pendidikan Sosial Finansial pada Anak Usia Dini menggunakan Media Loose Parts. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 4(2), 962. https://doi.org/10.31004/obsesi.v4i2.493 Wahyuningsih, S., Pudyaningtyas, A. R., Nurjanah, N. E., Dewi, N. K., Hafidah, R., Syamsuddin, M. M., & Sholeha, V. (2020). The Utilization of Loose Parts Media in Steam Learning for Early Childhood. Early Childhood Education and Development Journal, 2(2), 1. https://doi.org/10.20961/ecedj.v2i2.46326 Wardhani, W. D. L., Misyana, M., Atniati, I., & Septiani, N. (2021). Stimulasi Perilaku Sosial Anak Usia Dini melalui Media Loose Parts (Bahan Lepasan). Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(2), 1894–1904. https://doi.org/10.31004/obsesi.v5i2.694